Stunting Status and Child Development on Children Ages 1-5 Years in The Public Health Centre of Padamara District Purbalingga - Ningrum, Ema Wahyu; Utami, Tin (Jurnal Keperawatan Soedirman, 2018)
The prevalence of stunting has increased from 35.6% in 2010 to 37.2% in 2013. Children who suffer from stunting are at risk of delay in growth and development. The purpose of this study is to determine the relationship between stunting and development status of children under 5 years old. The research design was analytical survey with cross sectional approach. The number of sample were 60 children under 5 years old who selected through quota sampling technique. Microtoase stature meter, WHO anthro software and Denver sheet II were used to assess stunting and development status of children. Data was analysed using distribution frequency, chi square, fisher exact test, and Kolmogorov Smirnov. Result showed that there were no significant correlation between stunting and gross motor, fine motor, social and language development (p=0,649; p=1,000; p=1,000 and p=0.998 respectively). In conclusion, there is no relationship between stunting status and child development. However, mothers of children age less than 5 years old who suffers from stunting is suggested to pay attention to the developmental aspect of their children by taking regular screening and providing stimulation.